A critical analysis on the innkeepers act 1952 / Muhammad Syafiq Musa, Rabiatul Adawiyah Md Nordin and Fatin Zahirah Md Fuad - Musa, Muhammad Syafiq; Md Nordin, Rabiatul Adawiyah; Md Fuad, Fatin Zahirah (FAculty of Law, 2012)
There are several laws that govern the rights and liabilities of innkeeper. In Malaysia, the law that governs innkeepers is known as the Innkeepers Act 1952. There are similar laws that exist in United Kingdom which is known as the Hotel Proprietor Act 1956. In Australia, the law that governs the innkeepers is the Carriers and Innkeepers Act 1958. Although the provisions in the Innkeepers Act 1952 are quite similar with the innkeepers' law in other countries, but there are also some distinctions that can be drawn in which a reformation to the Act is necessary in order to improve the law of innkeepers. This aim of this study is to analyze the adequacy of the law and the extent of the legal rights of the guests and the liabilities of the innkeepers are being protected in Malaysia. In addition, this research is to suggest certain changes to the provisions of the Innkeepers Act 1952 regarding the liabilities of the innkeepers on the safety of the guests.